Estudio de factibilidad para la creación de una empresa productora comercializadora de galleta alfajor artesanal (2018)
In the present feasibility study for the creation of a marketing company for artisan biscuit alfajor in the city of Bogotá, it was possible to develop thanks to the opportunities found in the food subsector, currently has reinvented trends in food for humans with the need not to expose themselves to so many chemicals that currently adhere to food. We investigated the market and its initial demand for the development of the project, identifying the needs of the people thus obtaining the needs that can be met by attracting people and satisfying the need by consuming the product. A prototype is generated for the development of the project in facilities for the production and administration area which have their respective signage in occupational health and safety where the pleasant activity is developed. For creation and constitution there are legal parameters in areas such as environmental and legal for the implementation, additional financial knowledge is needed to determine if the project is feasible, viable and profitable.